Prevalence and factors associated with myopia in young (2017)
The prevalence of myopia varies in different populations in the world and the incidence increases in an accelerated manner, why refractive defects becomes a public health problem, with an economic and social impact. The progression of myopia can trigger pathological changes in the eyeball, affecting structures such as the lens, retina, choroid and macula. These degenerative changes are the most common cause of vision loss and are associated with an increase in refractive values that rise from childhood to adulthood. The development and progression are related to a genetic and hereditary component, however there is a complex interaction with external factors, which could explain the increase in cases among some populations, where increased urbanization and the need is perceived to achieve high levels of education. In addition, other environmental factors such as spend more time in the outdoors can be a favorable habit to prevent the onset of disease. © 2016 Sociedad Mexicana de Oftalmología